(3JTQja GdCjGe hGdYUhQ HSjQI Gdedc GdefUhQ (B( (3bdGhhf(B)s
(3ChdgG (B:s
(3ef SfI (B681(3g` s
(3BNQgG (B:s
(3Edi SfI (B689(3g` SfI haGI GdefUhQ bdGhhf s
(3hGdeLdOjf jZWjGf ef SfI (B681: 689(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B551 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B39 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs